Constitution, Viability and Productivity of Buttocksed Lambs in the Conditions of Karakalpakstan - Turganbayev R.U. (Zien Journals, 2022)
This article examines the constitution, viability and productivity of buttocksed,hisari,endemic and hybrid lambs in Karakalpakstan conditions and recommends selection elements aimed at increasing the number of sheep
Keywords: Genuses; constitution; productivity; ,viability